2021
DOI: 10.32535/apjme.v4i3.1270
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Organizational Culture and Competence on Employee Performance Mediated by Organizational Commitments in the Procurement of Goods and Services Secretariat Regency of Karangasem

Abstract: Employees have a very important role, where they must spare their energy and thoughts to achieve company goals. The management of corporate culture is directed to the ability to encourage company performance through improving employee performance. The purposes of this study are to examine and analyze the effect of organizational culture and competence on organizational commitment, employee performance, and employee performance. The population and the respondents were 76 people in the Karangasem Regency Governm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 8 publications
2
11
0
Order By: Relevance
“…Effect test results direct show that competence influential positive significant to commitment organization Where mark t statistics amounting to 2,484 and value p values of 0.013. Test results obtained show that hypothesis that has been developed can accepted as well as support results findings made by Suantara , et al (2020), Sumarsi & Rizal (2021) and Aryani, et al ( 2021) which concluded results that competence influential positive and significant to commitment organization .…”
Section: Influence Competence To Commitment Organizationsupporting
confidence: 84%
“…Effect test results direct show that competence influential positive significant to commitment organization Where mark t statistics amounting to 2,484 and value p values of 0.013. Test results obtained show that hypothesis that has been developed can accepted as well as support results findings made by Suantara , et al (2020), Sumarsi & Rizal (2021) and Aryani, et al ( 2021) which concluded results that competence influential positive and significant to commitment organization .…”
Section: Influence Competence To Commitment Organizationsupporting
confidence: 84%
“…Moreover, if language learning is not only related to linguistic aspects but requires knowledge or text as a source of information [8]. This means that the study also supports the proposition that a rhetorical text including speech offers a variety of information and knowledge related to values, culture and ideals that live in a nation that has a function to build society [28,34].…”
Section: Discussionsupporting
confidence: 73%
“…The meaning of speech and the mane'e ceremony can be used as one of the local wisdoms in the Sangihe Talaud area. Local wisdom is the ability to adapt, organize, and grow the influence of nature and other cultures that become the driving force for the transformation and creation of Indonesia's extraordinary cultural diversity [12,13]. It can also be a form of knowledge, belief, understanding or perception along with customary customs or ethics that guide human behavior in ecological and systemic life.So through the mane'e ceremony tradition, the Sangihe Talaud community can show other communities that the Mane'e community has a form of knowledge, belief, understanding or perception as well as habits in ecological life in Sangihe Talaud [14,15].…”
Section: Discussionmentioning
confidence: 99%